IMPROVE THE LEARNING OUTCOMES OF ARTS CULTURE AND WORKSHOP THROUGH ANIMATION FILM MEDIA - Lidya Maridha; Yun Ratna Lagandesa (Jurnal Dikdas, 2019)
The research aims to improve student learning outcomes through animated film media. The method used is Classroom Action Research (CAR). Based on the results obtained in this classroom action research, it can be concluded that there is an increase in student learning outcomes in class V SDN 11 Palu, seen from student learning outcomes in the implementation of pre-action, cycle I, and cycle II of 26 students. Student learning outcomes increase after researchers use learning media, namely Film Animation, through the Animated Film media students learn about a concept of drawing and coloring and facilitate teachers in conveying subject matter. Students who initially lack participation in learning, after being shown Animation Film students become motivated and more active in learning and have an impact on improving student learning outcomes, because in general students like Animated Films. This increase can also occur due to the role of the teacher. The teacher is a major factor in the success of learning. The teacher must be smart in choosing the right learning media in accordance with the material to be taught. In addition, the guidance and training provided by the teacher to students is also a very important factor.